ALLANITE-(CE) IN GRANITIC ROCKS FROM JAPAN: GENETIC IMPLICATIONS OF PATTERNS OF REE AND MN ENRICHMENT - Hoshino M.; Kimata M.; Shimizu M.; Nishida N.; Fujiwara T. (My University, 2006)
Twenty-two samples of allanite-(Ce) taken from granitic rocks in Japan have been characterized by electron-microprobe analysis. In back-scattered-electron (BSE) images, the allanite-(Ce) is homogeneous or characterized by various types of zoning features: oscillatory, normal or irregular types. Thirteen samples contain appreciable amounts of Mn (0.14-0.59 apfu). The Mn-rich crystals (2-6 cm long) are larger than the crystals of Mn-poor allanite-(Ce) (0.5-2 cm long). Samples of the two groups differ considerably from each other in chondrite-normalized REE patterns: Mn-poor allanite-(Ce) is relatively rich in LREE, as is common in igneous allanite, whereas the Mn-rich allanite-(Ce) exhibits an enrichment in the middle rare-earth elements (MREE). The relationship between Mn-rich and Mn-poor allanite-(Ce) is expressed by the coupled substitution Mn2+ + (MREE, HREE)3+ ⇌ Ca2+ + LREE3+. The presence of Mn-rich allanite-(Ce) in the Japanese island arc, in conjunction with occurrences of Mn-rich and REE-bearing epidote-group minerals in manganese deposits, support a link with subduction-zone processes. The granitic rocks containing Mn-poor allanite-(Ce) belong to the magnetite-series granitic rocks, whereas those containing Mn-rich allanite-(Ce) correspond to the ilmenite series, and seem to have formed from a volatile-enriched magma. Therefore, the Mn content in allanite-(Ce) contains petrogenetic information.
Keywords: ALLANITE-(CE); CHEMICAL ZONING; COUPLED SUBSTITUTION; CRYSTAL SIZE; GRANITIC ROCKS; JAPAN; MANGANESE; ORIGIN; RARE-EARTH ELEMENTS